A new switching law for event-triggered switched systems under DoS attacks. (August 2022) - Fu, Jun; Qi, Yiwen; Xing, Ning; Li, Yuzhe
Abstract: Networked control systems have unique advantages, but it might suffer from attacks, and the resulting asynchronous switching will greatly degrade the system performance and increase the difficulty of controller design. To address this challenge, in this paper, a new switching law and a resilient adaptive event-triggering strategy (RA-ETS) are proposed for networked switched systems to mitigate the negative impacts of asynchronous switching and denial of service (DoS) attacks By utilizing the new switching law, asynchronous switching is converted to expected and unexpected synchronous switchings. According to the minimum DoS sleeping time, the constraints on average dwell time and minimum dwell time are obtained for this switching law, and the sufficient conditions for the existence of expected synchronization are derived. Moreover, RA-ETS is designed to prevent the useless data during attacking from being triggered and to adjust the triggering frequency adaptively if no attacks. Subsequently, the stability of switched systems with an H ∞ performance index is ensured by virtue of the average dwell time method and piecewise Lyapunov–Krasovskii functional technique. In particular, the coupling relationship among the DoS attacking, expected and unexpected synchronous intervals is revealed. Finally, the effectiveness of the proposed approach is illustrated by a numerical simulation.